Bioprinting and biomaterials for dental alveolar tissue regeneration - Ostrovidov, Serge; Ramalingam, Murugan; Bae, Hojae; Orive, Gorka; Fujie, Toshinori; Shi, Xuetao; Kaji, Hirokazu (Frontiers in Bioengineering and Biotechnology, 2023)
Three dimensional (3D) bioprinting is a powerful tool, that was recently applied to tissue engineering. This technique allows the precise deposition of cells encapsulated in supportive bioinks to fabricate complex scaffolds, which are used to repair targeted tissues. Here, we review the recent developments in the application of 3D bioprinting to dental tissue engineering. These tissues, including teeth, periodontal ligament, alveolar bones, and dental pulp, present cell types and mechanical properties with great heterogeneity, which is challenging to reproduce in vitro. After highlighting the different bioprinting methods used in regenerative dentistry, we reviewed the great variety of bioink formulations and their effects on cells, which have been established to support the development of these tissues. We discussed the different advances achieved in the fabrication of each dental tissue to provide an overview of the current state of the methods. We conclude with the remaining challenges and future needs.